Loci of the genotyping panel by sequencing using AgriSeq technology in the Manych Merino breed - A. Yu. Krivoruchko; A. A. Likhovid; A. A. Kanibolotskaya; T. Yu. Saprikina; M. Yu. Kuharuk; O. A. Yatsyk (Аграрная наука Евро-Северо-Востока, 2023)
Using the genotyping of sheep of the Manych Merino breed on the basis of Illumina BeadChip Ovine 600K, loci suitable for genotyping by sequencing animals of this breed were found. Single nucleotide polymorphisms with a high frequency of occurrence in the range of 0.2850-0.3149 homozygotes of both wild and mutant variants were identified. Heterozygous variants of these substitutions occurred with a frequency of 0.379±0.012. The number of polymorphisms corresponding to the selected criteria was 521. Analysis of the location of the detected SNPs in the sheep genome showed their presence along the entire length of the genotyped DNA region. The largest number of polymorphisms were found on chromosomes 1, 2, 3, 17 and X. The least polymorphisms were detected on chromosomes 18, 21, 24 and 25. The resulting set of substitutions will effectively solve the problems of confirming the authenticity of the origin of sheep of the Manych Merino breed, accurately identify animals in the process of breeding work, and account for inbreeding in the population. The proposed set of SNPs is recommended both for use in genotyping by sequencing of a new generation, and for customization of SNP biochips.